Impact of Brain Fatty Acid Signaling on Peripheral Insulin Action in Mice - Neschen, Susanne; Wu, Moya; Fuchs, Christiane; Kondofersky, Ivan; Theis, Fabian J.; de Angelis, Martin Hrabě; Häring, Hans-Ulrich; Sartorius, Tina (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aims and Methods Glucose homeostasis and energy balance are under control by peripheral and brain processes. Especially insulin signaling in the brain seems to impact whole body glucose homeostasis and interacts with fatty acid signaling. In humans circulating saturated fatty acids are negatively associated with brain insulin action while animal studies suggest both positive and negative interactions of fatty acids and insulin brain action. This apparent discrepancy might reflect a difference between acute and chronic fatty acid signaling. To address this question we investigated the acute effect of an intracerebroventricular palmitic acid administration on peripheral glucose homeostasis. We developed and implemented a method for simultaneous monitoring of brain activity and peripheral insulin action in freely moving mice by combining radiotelemetry electrocorticography (ECoG) and euglycemic-hyperinsulinemic clamps. This method allowed gaining insight in the early kinetics of brain fatty acid signaling and its contemporaneous effect on liver function in vivo, which, to our knowledge, has not been assessed so far in mice.Results Insulin-induced brain activity in the theta and beta band was decreased by acute intracerebroventricular application of palmitic acid. Peripherally it amplified insulin action as demonstrated by a significant inhibition of endogenous glucose production and increased glucose infusion rate. Moreover, our results further revealed that the brain effect of peripheral insulin is modulated by palmitic acid load in the brain.Conclusion These findings suggest that insulin action is amplified in the periphery and attenuated in the brain by acute palmitic acid application. Thus, our results indicate that acute palmitic acid signaling in the brain may be different from chronic effects.
Keywords: brain; electrocorticography; euglycemic-hyperinsulinemic clamps; fatty acids; palmitic acid; radiotelemetry